Pengenalan dan Implementasi Standar Akuntansi Syariah bagi Guru MAN 3 Aceh Timur - Maknuni, Jauharil; Jamali (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
This activity aims to provide an in-depth understanding of the concepts, principles, and implementation of Sharia Accounting Standards in the context of Islamic economics in life in the business and community environment. This is also to supports the independent learning program whose sources come from various sources outside the school environment.In this activity, students are involved in a series of learning methods which include presentations, group discussions, case studies, guest speakers, exams/evaluations, and reflection sessions.These methods are designed to strengthen students' understanding of the basic principles of sharia accounting, ability to analyze sharia financial transactions, work in teams, and increase awareness of ethics in sharia accounting.The results of this activity indicate an increase in student understanding of the importance of sharia accounting standards, the basic principles of sharia accounting, as well as their ability to apply these principles in real situations in the surrounding community. In addition, students also succeed in developing analytical skills, teamwork, and awareness of ethics in sharia accounting. This activity is expected to provide long-term benefits for students in developing their careers and lives. With a deep understanding of Islamic Accounting Standards, students will become a generation that is competent in the field of Islamic accounting and can contribute to building an economy based on Islamic principles by continuing to innovate in the implementation of knowledge.